2021
DOI: 10.3389/fonc.2021.628007
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Adjuvant Stereotactic Radiotherapy of Motor-Eloquent Brain Metastases: Sparing the nTMS-Defined Motor Cortex and the Hippocampus

Abstract: Brain metastases can effectively be treated with surgical resection and adjuvant stereotactic radiotherapy (SRT). Navigated transcranial magnetic stimulation (nTMS) has been used to non-invasively map the motor cortex prior to surgery of motor eloquent brain lesions. To date, few studies have reported the integration of such motor maps into radiotherapy planning. The hippocampus has been identified as an additional critical structure of radiation-induced deficits. The aim of this study is to assess the feasibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Focusing on the nTMS-defined motor cortex, Tokarev et al (25) could reduce the maximum dose by up to 17% (average 6%) and the >12 Gy-volume by 2-78% (average 35.2%) in eight patients planned using GammaKnife. For linearaccelerator-based treatment of brain metastases, Schwendner et al (22) reported a mean dose reduction to the nTMS-based motor cortex of 18% for a collective of 30 patients planned with VMAT, which corresponded to our own results for patients with metastases treated with IMRT, non-coplanar arcs, or static beams [sparing of about 30% in mean dose, but depending on planning technique and distance between the lesion and the motor cortex, (26)].…”
Section: Comparison With Previous Studies On Ntms-based Motor Cortex ...supporting
confidence: 80%
See 2 more Smart Citations
“…Focusing on the nTMS-defined motor cortex, Tokarev et al (25) could reduce the maximum dose by up to 17% (average 6%) and the >12 Gy-volume by 2-78% (average 35.2%) in eight patients planned using GammaKnife. For linearaccelerator-based treatment of brain metastases, Schwendner et al (22) reported a mean dose reduction to the nTMS-based motor cortex of 18% for a collective of 30 patients planned with VMAT, which corresponded to our own results for patients with metastases treated with IMRT, non-coplanar arcs, or static beams [sparing of about 30% in mean dose, but depending on planning technique and distance between the lesion and the motor cortex, (26)].…”
Section: Comparison With Previous Studies On Ntms-based Motor Cortex ...supporting
confidence: 80%
“…Beyond sparing the nTMS-defined motor cortex, we emphasize the importance of maintaining hippocampus sparing. In a previous study for brain metastases, we could show that the inclusion of motor cortex objectives in treatment planning without additional hippocampus objectives may even increase hippocampus dose (26). Hence, we here assess the possibility of the combined motor cortex and hippocampus optimization in radiotherapy treatment of glioblastoma (GBM).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many sites require dose control during irradiation. The brainstem, hippocampus, temporal lobe, optic nerve and auditory nerve are common sites where long-term clinical damage can occur due to radiation therapy [24]. Physician-controlled doses to organs in the brain are generally as low as possible.…”
Section: Sbrt For Organ Protection In Brain Metastasesmentioning
confidence: 99%
“…Repeated exposures with doses of 100 mGy (0.1 Gy) have been shown to compromise the structural and functional integrity of hippocampal neurogenesis which has been associated with neurocognitive dysfunctions that affect learning and memory [4][5][6][7]. Numerous clinical studies have aimed to reduce the hippocampus dose in brain radiotherapy by hippocampus-avoiding dose distributions [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%